84. A Survey Based Assessment of Provider Practice Around Obtaining Repeat Blood Cultures. (4th December 2021) - Govindan, Sujeet; Strnad, Luke
Abstract: Background: Apart from Staphylococcus aureus and Candida species, there is little guidance on whether to obtain repeat blood cultures after an initial positive set. We have noted heterogeneity in practice amongst our Infectious Disease (ID) group at Oregon Health and Science University (OHSU) and suspect there is heterogeneity amongst adult hospitalist providers as well. Methods: We created a survey using clinical vignettes encompassing commonly encountered scenarios among hospitalized patients on medical wards to assess provider practices in obtaining repeat blood cultures. The survey was sent to adult ID providers and adult hospitalist providers at OHSU. These vignettes represented 9 of the most common bacteria seen in positive blood cultures and asked the question of whether providers would obtain repeat blood cultures after an initial positive set. The organisms included beta hemolytic streptococcus, Enterococcus faecalis, Streptococcus gallolyticus, coagulase-negative staphylococci, alpha hemolytic strep, E coli, Proteus mirabilis, Pseudomonas aeruginosa, and Bacteroides fragilis . We then asked questions around repeat blood culture practices for Staphylococcus aureus and Candida species, understanding that while repeat blood cultures for these organisms is recommended, the manner in which individual providers implement this may vary. Results: The survey response rate was 45%. Results were heterogenous with only 3 questions having inter- and intra- group agreement. Those 3 questions represented a case of E faecalis bacteremia without known source, a case of asymptomatic Staphylococcus epidermidis blood culture positivity, and a case of E. coli bacteremia from a pyelonephritis. All other vignettes had inter- and intra- group differences signifying clinical uncertainty around the practice of obtaining repeat blood cultures. There was similar heterogeneity among the responses asking how providers obtain repeat blood cultures around S. aureus and Candida bloodstream infections. Clinical vignette survey answers Answers from 10 clinical vignettes on obtaining repeat blood cultures after an initial positive set for stable patients on medical wards. Staphylococcus aureus Candida sp Conclusion: There is significant heterogeneity amongst adult ID and hospitalist providers on what organisms and situations should prompt repeat blood cultures. There are differences around how repeat blood cultures should be obtained, including for Staphylococcus aureus and Candida sp. Disclosures: All Authors : No reported disclosures